Diagnostic In Vivo Sensing of COVID-19 Antibody Detection Using DNA-Linking Graphene Oxide Synthetic Mimic Skin Tattoo Probes - Kyung Lee; Dong Ho Kim; Sihyun Jun; Yeseul Oh; Ye Jun Oh; Seo Jun Lee; Keumsook Kim; Suw Young Ly (Microorganisms)
COVID-19 antibody detection is dependent on highly specialized, time-consuming techniques, such as PCR separation, DNA amplification, and other methods such as spectrophotometric absorption. For these reasons, specialized technical training is necessary because individual diagnostic treatment is difficult. We have attempted to perform rapid sensing with a detection time of only 30 s. Additionally, we used a wearable multi-layer graphene oxide nanocolloid synthetic skin tattoo probe assay for influenza and COVID-19 virus detection with an electrochemical antigen–antibody redox ionic titration circuit. Cyclic voltametric−2 V~2.0 V potential windows were used. The diagnostic detection limit was determined using stripping anodic and cathodic amplifiers, and the working probe was fabricated with a graphene molecule structure with a virus antigen-immobilized amplifier. With redox potential strength obtained within −1.0 V~−1.3 V ionic activity, anodic and cathodic current linearly increased in the phosphate-buffered saline 5 mL electrolyte. The results indicate that instant detection was enabled via individual and wearable tattoo sensors.